First Record of Trichurus spiralis Hasselbring on Seeds of Acacia nilotica : a New Report - Soni, K. K.; Purohit, Mamta; , Jamaluddin (Indian Forester, 2010)
Thirteen different provenances of Acacia nilotica were collected from different agroclimatic zones of India. Before sowing in the field, all the provenances were tested for seed mycoflora and germination. Large number of fungi belonging to different taxonomic groups were identified from seeds of A. nilotica. Aspergillus terreus showed the highest dominance in different provenances. The frequency of fungi was less in the provenances of Mandla and Jabalpur. A fungus Trichurus spiralis was recorded first time only on 6 provenances. The fungus was secreting the inhibitory substances, which possibly reduced the germination of seeds.